A SURVEY OF SELECTED ENVIRONMENTAL ASPECTS IN MANUFACTURING COMPANIES (Perner's Contacts, 2013)
The article presents the results of a survey conducted in the in May 2013. The article is centered on some issues in ecology of manufacturing companies and their logistics. Presented survey is concerned in the representation of ISO 14001 certificate in the surveyed companies, in the declaration of environmental friendliness as part of a business strategy, farther in indication of the proportion of recycled materials in production and whether the environmental friendliness is declared as a high value among the other categories of value in terms of logistics processes. This article presents the differences between large, medium-sized and small companies in these aspects.